Measles Enteritis in Infants and Children - Indra Tamboen; Atan Baas Sinuhaji; A. H. Soetanto (Indonesian Pediatric Society, 1991)
The incidence, mortality and clinical features of measles enteritis were reported among 6484 infants and children admitted to the Pediatric Ward Dr. Pirngadi General Hospital Medan from 1st January J987 until 31st December 1988. Of these 6484 children, 2685 suffered from gastroenteritis and 82 from measles. There w,ere 31 cases of measles enteritis (1 .2% of all gastroenteritis cases or 37.8% of measles cases). Most of measles enteritis cases (74.2%) were in the age group of 6-24 months and no case was found under six months old. The mortality of measles enteritis with bronchopneumonia and encephalitis was 25.0% while the mortality of measles enteritis with bronchopneumonia was 13.3%. There were no deaths in children just with measles enteritis alone. The overall mortality of measles enteritis with or without accompanying disease was 12.9%. The age specific death rate of measles enteritis was highest (23.1 o/o) in the 13-24 month age group.